Professionalization Pathways for School Leaders Examined: The Influence of Organizational and Didactic Factors and Their Interplay on Triggering Concrete Actions in School Development - Els Tanghe; Wouter Schelfhout (MDPI AG, 2023)
It is believed that school leadership contributes to efficiency and equity in school performance. Therefore, it is essential that professionalization initiatives for school leaders foster learning and development processes towards effective leadership. Based on a literature review, several factors appear to facilitate the influence of professionalization programs on learning outcomes of school leaders but empirical research on real effects and on explanatory processes is limited. This research gap forms the basis for this mixed methods study, in which we design and implement a longitudinal professionalization program as the research setting. We distinguish an organizational dimension focusing on structural choices and an intertwined didactic dimension. We examine which specific interaction between both contributes most to concrete learning-driven actions at the school of the participant. The results indicate that by participating in the program with such a design, school leaders prepare action plans for their own school and start up school development. The interaction between actively providing theoretical frameworks, further deepening insights through peer learning in professional learning communities, the conversion of insights into concrete action plans and supporting this with school-specific coaching leads to the strongest results, analyses show.